Modern neural network method evaluation model security settings resources information systems - Корченко, Олександр Григорович; Терейковський, Ігор Анатолійович; Дзюбаненко, Андрій Васильович (Ukrainian Information Security Research Journal, 2015)
One of the main obstacles to widespread adoption of neural network methods and models in cyber attacks and detection systems to detect vulnerabilities in the systems resources information systems is the lack of options on which to evaluatetheir effectiveness. Also, there are no methods forassessing the effectiveness and implementation of such. Tosolve this problem has been analyzed a wide range of modern neural network methods and models used in the detection systems. The list of parameters and a method of theiruse for assessing the effectiveness of the design and selectionof these methods and models in the construction of these detection systems. The obtained results allow us to determinethe shortcomings of modern neural network detectiontools and means of cyber vulnerability detection and outlinepromising ways to improve them.